Study of the electrical properties of Ion Beam Sputtered thin AlNiCo films (Baghdad Science Journal, 2007)
The electrical properties of the AlNiCo thin films with thickness (1000oA) deposited on glass substrates using Ion – Beam sputtering (IBS) technique under vacuum